PERBEDAAN DIALEK JAWA DI DESA TEGALPINGEN DAN DESA REJAMULYA SERTA IMPLEMENTASINYA TERHADAP KETERAMPILAN BERBICARA SISWA SMK - Amalia Nur Hidayati; Hidayat Nur Septiadi; Sigit Andi Prasetya Dinata (CV. Denasya Smart Publisher, 2025)
This study examines the differences in Javanese dialect vocabulary between Tegalpingen Village, Pengadegan District, Purbalingga Regency, and Rejamulya Village, Kedungreja District, Cilacap Regency, as well as their implications for students’ speaking skills. The research was motivated by observations of variations in vocabulary, phonological, and semantic aspects that affect communication among students at SMK YPLP Perwira 2 Purbalingga and SMK LPPM RI 2 Kedungreja. Using a descriptive qualitative method with a sociolinguistic dialectology approach, the study found phonological differences such as phoneme addition (prothesis, epenthesis, paragoge) and phoneme reduction (aphaeresis, syncope, apocope), along with contraction, substitution, and metathesis processes. Specifically, 27 vocabulary items involved phoneme changes, 4 prothesis, 8 epenthesis, 3 paragoge, 8 aphaeresis, 5 syncope, 2 apocope, and 1 metathesis. Semantic differences included 51 synonymic terms, where different words refer to the same concept, and 5 homonyms, where identical forms have distinct meanings. The implementation of these dialectal differences revealed that students tend to feel more confident using local dialects in daily conversations, yet they face difficulties when required to use standard Indonesian, particularly in distinguishing between polite and impolite registers. Interviews with language teachers further indicated that Javanese dialect use in school settings often carries negative stigma, highlighting the need for guidance in applying appropriate language varieties in both peer and teacher interactions.